Novel hydroxide precursors for low temperature synthesis of selected ternary oxides - Muthurajan, H.; Rao, N. Koteswara; Gupta, U. N.; Pradhan, Sivaram; Jha, Ratnesh Kumar; Kumar, H. H.; Mirji, S. A.; Ravi, V. (Materials Research Bulletin, 2008)
A novel method of using hydroxide precursors to reduce the synthesis temperature for few selected ternary oxides has been presented here. This technique is very useful and advantageous when the ternary oxides contain an alkaline earth element. The selected compositions for this method are BaCeO3 (BC), BaBiO3 (BB), La0.7Sr0.3CoO3 (LSCO) and BaBi2Nb2O9 (BBN). Commercially purchased strontium (or barium) hydroxide and freshly prepared lanthanum, cobalt, bismuth and niobium hydroxides were mixed thoroughly in stoichiometric ratio and heated at different temperatures ranging from 100 to 700 degrees C for 10 h for corresponding compositions. The sequence of the reaction and evolution of the product phase were studied by the X-ray diffraction (XRD) studies. The phase purity and lattice parameters were also determined by XRD investigations. All the product phases in each case were formed at relatively low temperature than when they were prepared by co-precipitation or solid state method. The morphology and average particle size of these powders were investigated by scanning electron microscopy (SEM). (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Novel hydroxide precursors to prepare NaNbO3 and KNbO3 - Muthurajan, H.; Kumar, H. H.; Samuel, V.; Gupta, U. N.; Ravi, V. (Ceramics International, 2008)
Firstly, fresh niobium, hydroxide was precipitated from NbF5 solution using an aqueous ammonium hydroxide under basic conditions. Then a simple procedure of mixing potassium (or sodium) and niobium hydroxides together and heating at a low temperature (<400 degrees C) produced KNbO3 (KN) or NaNbO3 (NN) powders. This is the lowest temperature so far reported for the formation of these phases. The phase content and lattice parameters are determined by X-ray diffraction (XRD). The average particle size and morphology were studied by scanning electron microscopy (SEM). (c) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: chemical preparation; niobates; Perovskites; powders; X-ray methods

Novel technique to prepare LiTaO3 at low temperature - Muthurajan, H.; Kumar, H. H.; Natarajan, N.; Ravi, V. (Ceramics International, 2008)
Firstly, fresh tantalum hydroxide was precipitated from TaF5 solution using an aqueous ammonium hydroxide under basic conditions. Then a simple procedure of mixing lithium and tantalum hydroxides together and heating at a low temperature (450 degrees C) produced pure ultrafine single phase LiTaO3 (LT). This is the lowest temperature so far reported for the formation of LT in the literature. The phase content and lattice parameters are determined by X-ray diffraction (XRD). The average particle size and morphology were studied by transmission electron microscopy (TEM). (c) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: chemical synthesis X-ray diffraction; Electron microscopy; electronic materials; LiTaO3